Characterization of Aluminum Alloy–Silicon Carbide Functionally Graded Materials Developed by Centrifugal Casting Process - Ioan Milosan; Tibor Bedő; Camelia Gabor; Daniel Munteanu; Mihai Alin Pop; Dorin Catana; Mihaela Cosnita; Béla Varga (Applied Sciences, 2021)
The continuous development of modern industries rises the necessity for functionally graded materials. This research starts from the consideration that the incorporation of SiC particles in the molten aluminum alloy can be difficult due to the very low wettability of SiC particles. In order to increase their wettability, SiC particles were covered with a layer of metallic copper. The incorporation of SiC particles into the aluminum alloy mass was performed by centrifugal casting. The secondary hypoeutectic Al-Si alloy used in this study was elaborated within the crucible of a resistors heated furnace. The metallic coating of SiC particles, in addition to the effect of increasing their wettability by molten metal, also has a role in preventing the formation of aluminum carbide in case of heating above 700 °C. A great amount of attention was paid to the parameters used during the centrifugal casting process. The results showed that adjusting the proportion of SiC particles within the composite allows us to obtain values of the thermal expansion coefficient within previously established limits. The present work demonstrates that the coating of SiC particles covered with a thin layer of metallic Cu creates the conditions to easily incorporate them into the molten Al mass, thus obtaining FGMs with controlled properties.